Capnographic identification of end-expiratory flow limitation - Dueck, Ron; Wong, Eric G.; Prisk, G. Kim; Hastings, Randolph H. (Respiratory physiology & neurobiology, 2018)
•Expired CO2 rises near the end of an exhalation to residual volume.•The CO2 rise tracks expiratory flow limitation (EFL), analogous to phase V for N2.•Anesthetized patients can have EFL at normal tidal volumes.•Phase V could be a capnographic marker for EFL during anesthesia. Patients with end-expiratory flow limitation (eEFL) demonstrate a terminal rise in capnography slope. The high slope could represent phase 5, a phenomenon described for single breath N2 tests but previously unreported during capnography. This study evaluated 6 healthy subjects exhaling from total lung capacity to residual volume at several set constant rates. We measured the volumes of flow limitation (VFL) and phase 5 (VP5) for CO2 and N2. A distinct phase 5 occurred shortly after eEFL for both gases. Increased expiratory flow rate resulted in parallel increases in VFL and VP5. The two quantities differed on average by the volume of dead space. These data suggest that phase 5 on capnography identifies eEFL with a small delay resulting from transit of expired gas through dead space. Following phase 5 by volumetric capnography could be useful for monitoring anesthetized patients, who in some circumstances may have lung volumes close to residual volume. eEFL could be treated with lung volume-increasing maneuvers, such as positive end-expiratory pressure.